The Religious Status of Women in the Old Testament, Veiling According to the Jewish Holy Books - Alaskarova, Parı Alaskarova (Scholarya Demo Journal of Ruby, 2023)
The role of women in creation and religious life according to Jewish primary sources, as well as the tradition of women’s veiling according to Jewish holy books, are investigated in the article. Such a subject has been addressed in order to contribute to the History of religions in our country. Additionally, it intends to convey the information that women should veil in other religions as well through Judaism to those who limit the veil only to Islam. This article is research based on a literature review. The study consists of an abstract, an introduction, three subheadings, a conclusion and a bibliography. • The creation of women in the Old Testament has been analyzed according to Yahwist and Elohist texts. In both texts, the story of the creation of women is described differently. Specifically, in the Elohist text, women are presented as equal to men, whereas in the Yahwist text, they are described as servants to men. • The religious status of women in the Old Testament includes issues such as individual and congregational worship of Jewish women, Torah reading, Torah teaching and learning, and women’s prayer groups. Unlike men, in individual worship, women are not permitted to recite all the prayers during worship, nor they can wear tefillin and tzitzit. Women are not counted as part of the congregation and cannot read or teach the Torah. Women are only required to light the Hanukkah candle, recite Kiddush on Shabbat evenings, fast on Yom Kippur, and fulfill a few other commandments. • The Old Testament, the Mishnah, and the Talmud contain information about the veiling of women. The veils of free and chaste women were distinguished from those of prostitutes, slaves, and concubines. While free women wore veils, prostitutes used colorful and different styles of covering. The hair of married slave women was cut to make them more distinguishable. Although in the course of time wigs replaced the veil, today only Orthodox women wear wigs during prayer.